Numerical Study on the Anti-Snow Performance of Deflectors on a High-Speed Train Bogie Frame - G. Gao (Journal of Applied Fluid Mechanics, 2020)
In this paper, a new installation of flat plate deflector which attached on the bottom of the bogie frame is proposed and its anti-snow accumulation performance with different attack angles is numerically studied. The wind-snow two-phase flow in the bogie region is simulated based on the Reynolds Averaged Navier-Stokes (RANS) equations combined with the Realizable "k-ε" turbulence model and the Lagrangian particle phase method. The adopted numerical simulation methodology is verified and validated by comparing with previous wind tunnel tests. In this paper, three typical attack angles (30°, 60°, 90°) for deflector are studied. The results show that: the 30° case has a medium influence on the flow field and reduces snow accumulation by 35.14%; the 60° case guides the high-speed airflow downward and has the best effect with 62.46% reduction in snow accumulation; the 90° case has the smallest reduction with 20.30% in the mass. Overall, all deflectors with three different installation angles can reduce the mass of snow accumulated on the bogie surface.